A review of spatial structure of freshwater food webs: Issues and opportunities modeling within‐lake meta‐ecosystems. Issue 8 (9th June 2022) - Borrelli, Jonathan J.; Relyea, Rick A.
Abstract: Lakes are currently facing multiple anthropogenic stressors impacting their ecological communities. The best way to understand how these systems will be affected by the changing environment is by modeling community dynamics. Models of lake food webs have tended to focus on pelagic organisms and treat lakes as if they contain single, uniform communities. However, heterogeneity in environmental conditions and resource availability generates within‐lake compartmentalization in food web structure. Turnover among species and their interactions resulting from differences in depth and substrate type creates unique food webs in different regions of lakes. Food webs within lakes can therefore be represented as a three‐dimensional meta‐ecosystem, where food web compartments are connected by flows of nutrients, materials, and consumers with variable degrees of mobility within the lake. We review how food webs are spatially structured within lakes and the processes that connect different parts of the ecosystem. We then discuss how current modeling approaches address the spatial heterogeneity of lake communities, highlighting key methods and some of the constraints preventing more spatially explicit representation of food webs. Finally, we recommend the use of allometric trophic networks to make spatially explicit food web modeling easier. By capitalizing on empirically described allometric relationships to parameterize trophically complex food webs, we can balance generalizable model approaches with system‐specific needs. Given the spatially explicit nature of many current threats to freshwater lakes, building an understanding of how space structures the community is imperative to create better approaches for freshwater management and conservation.